The study of in vitro superfused spiral modiolar artery bioassay on the endothelin-1 antagonistic activity of (+)-myriceric acid a and its novel synthetic tetracyclic terpenoids intermediates - Bao, Weier (Kansas State University, 2010)
(+)-myriceric acid A is known as a non-peptide ETA receptor antagonist. It is isolated from the natural plant Myrica cerfera with 0.01% yield which is very low. The total synthesis of (+)-myriceric acid A is being pursued in Hua’s lab. (+)-myriceric acid A specifically blocks the vasoconstriction caused by endothelin-1 (ET-1). Because some derivatives of (+)-myriceric acid A were shown to have ET-1 receptor antagonistic effect, the tetracyclic terpenoid intermediates toward the total synthesis of (+)-myriceric acid A are postulated to have the similar antagonistic activities. The objective of this project is to study the release of vasoconstriction of these synthetic intermediates and compare their antagonistic potency. The ET-1 receptor antagonistic bioactivity of six (+)-myriceric acid A intermediates as well as (+)-myriceric acid A were evaluated by the in vitro spiral modiolar artery (SMA) bioassay. The synthetic intermediates which have not been reported in the literature were previously synthesized in Hua’s laboratory by Dr. Angelo Aguilar and Dr. Aibin Shi. Their synthesis was described in Dr. Aguilar’s PhD thesis. All the antagonistic effect evaluations were based on the SMA’s diameter changes. SMA’s diameter changes were induced by the superfusion of different extracellular solutions. The dose-response curves and straight lines were plotted to compare the antagonistic potency of these compounds. Based on the EC50 value of (+)-myriceric acid A intermediates (0.090 µM ~ 0.582 µM for the curves and 0.095 µM ~ 0.385 µM for the straight lines), all of the compounds have ET-1 receptor antagonistic activity, therefore the synthesis and screening of (+)-myriceric acid A intermediates is probably a promising route to develop new non-peptide ETA receptor antagonists.
Keywords: (+)-myriceric acid A intermediates; endothelin-1; spiral modiolar artery; Chemistry, Biochemistry (0487)